ECG-monitoring of in-hospital cardiac arrest and factors associated with survival. (May 2020) - Thorén, Anna; Rawshani, Araz; Herlitz, Johan; Engdahl, Johan; Kahan, Thomas; Gustafsson, Linnéa; Djärv, Therese
Abstract: Background: ECG-monitoring is a strong predictor for 30-days survival after in-hospital cardiac arrest (IHCA). The aim of the study is to investigate factors influencing the effect of ECG-monitoring on 30-days survival after IHCA and elements of importance in everyday clinical practice regarding whether patients are ECG-monitored prior to IHCA. Methods: In all, 19.225 adult IHCAs registered in the Swedish Registry for Cardiopulmonary Resuscitation (SRCR) were included. Cox-adjusted survival curves were computed to study survival post IHCA. Logistic regression was used to study the association between 15 predictors and 30-days survival. Using logistic regression we calculated propensity scores (PS) for ECG-monitoring; the PS was used as a covariate in a logistical regression estimating the association between ECG-monitoring and 30-days survival. Gradient boosting was used to study the relative importance of all predictors on ECG-monitoring. Results: Overall 30-days survival was 30%. The ECG-monitored group (n = 10.133, 52%) had a 38% lower adjusted mortality (HR 0.62 95% CI 0.60−0.64). We observed tangible variations in ECG-monitoring ratio at different centres. The predictors of most relative influence on ECG-monitoring in IHCA were location in hospital and geographical localization. Conclusion: ECG-monitoring in IHCA was associated to a 38% lower adjusted mortality, despite this finding only every other IHCA patient was monitored. The significant variability in the frequency of ECG-monitoring in IHCA at different centres needs to be evaluated in future research. Guidelines for in-hospital ECG-monitoring could contribute to an improved identification and treatment of patients at risk, and possibly to an improved survival.